COGNITIVE BEHAVIOURAL THERAPY: A MAGIC TO SPRING TECHNOLOGICAL ANTIDOTE FOR THE CURTAILMENT OF CONSTERNATION AND EXPANSION OF ELOQUENCE IN ENGLISH LANGUAGE. - Menon, Rethy B.; Martin, Amrutha; R, Asha T (International Journal of Psychosocial Rehabilitation, 2020)
An individual can survive confidently, independently and courageously in this corporate world only if he/she is fluent in English language. The objective of this study is to seek the effectiveness of CBT in reducing the consternation and enhancing the fluency in English language. It signifies the correlation between the effects of consternation on the fluency of English. The experimental design used is one group Pre-test and Post-test design. The sample selected for the study is students of remote area; sample size is 21 students belonging to high school. Consternation regulating capacity scale and Achievement test of English language were used as the Pre-test and Post-test tool for data collection. The statistical techniques used are descriptive statistic, t-test and paired t-test. The findings showed that CBT is much effective in reducing the consternation and enhancing the achievement in English language.